Toxicological Investigation of Acute Cyanide Poisoning Cases: Report of Four Cases - Humera Shafi; Muhammad Imran; Hafiz Faisal Usman; Muhammad Zar Ashiq; Muhammad Sarwar; Muhammad Ashraf Tahir (Arab Journal of Forensic Sciences & Forensic Medicine, 2015)
Cyanide is a deadly poison. Acute cyanide poisoning in humans is rare and is predominantly caused by smoke inhalation from fires and much more rarely by intentional ingestion of cyanide salts as in suicide or homicide attempts. The main objective of this report is to emphasize the need to consider cyanide poisoning, even if it is rare, in differential diagnosis while evaluating cases of sudden death and the significance of gastric content analysis in acute poisoning cases. The authors reported four cases of lethal cyanide poisoning. Autopsy specimens were submitted to the author’s laboratory for analysis. A presumptive test for cyanide using Vitamin B12 indicated the presence of cyanide. Confirmation and quantification of cyanide was performed using headspace gas chromatograph coupled to flame ionization detector technique. The toxicological analysis revealed lethal hydrogen cyanide concentrations in all postmortem specimens ranging from 24 to 2600 mg/L in gastric contents, 70 to 282 mg/kg in liver specimens, 11 to 12 mg/kg in a mixture of viscera (liver, spleen, kidney) and 15 mg/L in blood. The cause of deaths in the reported cases was acute respiratory failure and cardiac arrest following cyanide intoxication.